Aesthetics of Employing Mirrors in the Residential Interior Spaces (Al-Academy, 2025)
The problem of the present research is defined by the following question: (Does employing mirrors succeed in achieving innovative and novel aesthetics in residential interior designs?). The research also aims to discover the aesthetics of mirrors and how they are employed in residential interior designs. The research is limited to the interior designs in Erbil from 2006 to 2023.Chapter Two consists of three sections. Section one deals with mirrors, their types, and characteristics. Section two deals with the interior design, its elements, materials, and the accessories used in the interior design. The third section introduces mirrors and the ways of employing them in the interior design. Chapter Three includes the research procedures in that its sample consists of (nine) models of the interior designs of houses in Erbil.The researcher analyzes two of them. Moreover, the researcher used the descriptive analytical method in his analysis. In Chapter Four, the researcher analyzes the research samples and then introduces the results achieved. The most important ones are that innovatively using mirrors, crossed and broken, and in stenographic forms, positively affect the interior space. Further, mirrors work as an extending or expanding factor to a space, unite the interior design, and reflect the width. Finally, using mirrors within a complicated geometrical composition increases and strengthens space aesthetics and light distraction in addition to its distribution in a way that does not cause boredom.The research ends with chapter five by introducing some conclusions, recommendations, and suggestions.